The Reduction of Cholesterol with Cupping Therapy on Cholesterol Reduction in Patients with Hypercholesterolemia - Zahid Fikri; Nursalam Nursalam; Eka Mishbahatul Mar'ah Has (Universitas Airlangga, 2010)
Introduction: Hypercholesterolemia is a risk factor causes of death at younger ages. Hypercholesterolemia may increase the risk of atherosclerosis, coronary heart disease, pancreatitis (pancreas inflammation in organs), diabetes mellitus, thyroid disorders, liver disease and kidney disease. Many patients with hypercholesterolemia using cupping therapy. Cupping therapy is alternative treatment process of throwing dirty blood from the body through the skin surface. The objective of this study was to determine the effect of cupping therapy to decrease cholesterol levels in patients with hypercholesterolemia.Method: Design used in this study was quasy experimental design. The population is all patients with hypercholesterolemia in the health center plaza Gresik. The total sample is 18 respondents, taken according to inclusion criteria. Independent variable is the cupping therapy. The dependent variable was the decrease in cholesterol levels. Data were collected using a questionnaire and observation of cholesterol. Data were analyzed using independent t-test and paired t tests with signi fi cance level α < 0.05.Result: The results show that cholesterol levels in patients with hypercholesterolemia treated groups decreased majority. Independent statistical analysis using t-test showed p = 0.001 and with the Paired t-test p value = 0.003.Discussion: This result means that there are significant effects of cupping therapy on cholesterol reduction in patients with hypercholesterolemia aged 45 years and over. Further research needs to be done in control diet, lifestyle and daily activities for the success of cupping therapy.